Pengaruh laju pemanasan dan variasi komposisi limbah paduan aluminium dengan Fly Ash Batubara terhadap kekerasan dan kekuatan tekan produk metalurgi serbuk - A.A.A. Triadi; P.D. Setyawan; I.K. Kurniawan (Universitas Mataram, 2023)
In this study, the manufacture of composites using the powder metallurgical method used two research variables, namely the rate of heating with variations in temperature with an increase of 3Ã‚Â°C/minute, 5Ã‚Â°C/minute and an increase of 7Ã‚Â°C/minute.Ã‚Â The second variable is the mixing composition with variations in aluminium composition: Fly Ash is 100%:0%, 85%:15%, 80%:20% and 75%:25%.Ã‚Â The highest hardness results in this study were found in the 15% fly ash composition with a heating rate of 3Ã‚Â°C/minute where the hardness value was 66.17 HRF while the lowest hardness value was found in the 0% fly ash composition with a heating rate.Ã‚Â of 7Ã‚Â°C/min with a hardness value of 34.84 HRF.Ã‚Â For compressive strength test results.Ã‚Â the highest value was obtained in the 15% Fly Ash composition with a heating rate of 3Ã‚Â°C/minute where the compressive strength value was 106.78 MPa, while the lowest compressive strength value was in the 0% fly ash composition with a heating speed of 7Ã‚Â°C minutes where the value was 42.71 MPa.Ã‚Â From the hardness and compressive strength value, it can be concluded that the smaller the heating rate, the higher the hardness and compressive strength and the greater the SC mixing composition, the higher the hardness and compressive strength.